Edith Stein – a Daughter of the Jewish Nation - Rastoin, Cecile (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
This article discusses the rich relation between Judaism and Christianity, one of the issues addressed by Stein in her intellectual explorations, as well as a matter pivotal in her life. By referring to Stein’s texts, her letters and other documents, as well as a claim made by commentators of her work and life, the author tries to expose numerous falsities and myths that arouse about Stein’s life. Beginning with an overview of Judaic tradition in which Stein grew up, the author then depicts the socio-political situation of Breslau as well as Stein’s family history. Next, C. Rastoin emphasises the moment when Stein recognised the power of Cross and joined the Catholic Church, yet at the same time did not cease to love the Jewish nation or feel a member of it. The last part of the text outlines Israel’s theology as well as a request for Judeo-Christian reconciliation and reciprocal respect.